Assessment of Palatal Height Index and palatal form in different malocclusions in adult patients visiting Nishtar Institute of Dentistry, Multan - Khalid, Asia; Rasheed, Faisal; Awaisi, Zubair H. (Orthodontic Journal of Nepal, 2021)
Introduction: This study was conducted to evaluate the palatal height index in different malocclusion because of appearance of variable palatal heights & palatal forms Materials & Method: In this study 108 adult subjects (41 males, 67 females), age ranges from 13-28yrs, were randomly selected from Orthodontic Department In Nishtar Institute of Dentistry Multan. Their impressions were taken by the Alginate and dental casts were formed and lateral cephalograms were collected. One sample t test was used to calculate the results. Result: Descriptive statistics showed mean palatal index of 60.95% in skeletal class I, 48.31% in skeletal class II, whereas 61.26% in skeletal class III. Frequency distribution in different skeletal patterns showed 100% high palate in class I and class III whereas skeletal class II showed variety in palatal form with 82.3% high palate, 11.3% medium palate and remaining 6.3% was low palate. major portion of the sample had high palate. Conclusion: Mean index in Skeletal Class I is 60.95 %, 48.31% in skeletal class II, 61.26% in skeletal class III. Mean palatal height index in females is significantly higher than in males. Skeletal class II has variety of palatal form with high prevalence of high palate. Most common palatal form is high palate.